Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1177/019262339602400407
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Dental Lesions in Ovariectomized Rats

Abstract: The effects of cadmium chloride on both incisor and molar teeth of ovariectomized female rats were studied histopathologically. The rats were injected intravenously with the compound at doses of 1.0 and 2.0 mg/kg, 5 days/wk. Six rats per group were sacrificed at 4, 8, and 13 wk.Discoloration of the incisors was observed in the rats of the 2.0-mg/kg group from 8 wk. Histopathologic examination of the incisor demonstrated decreased iron-containing pigment in ameloblasts and destruction of the enamel organ. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Katsuta et al (1996) studied the effects of cadmium in molar and incisive teeth and observed a reduction at iron pigment in ameloblast cells and damage at enamel organ of incisive teeth. Following iron reduction, cadmium accumulation increased in teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Katsuta et al (1996) studied the effects of cadmium in molar and incisive teeth and observed a reduction at iron pigment in ameloblast cells and damage at enamel organ of incisive teeth. Following iron reduction, cadmium accumulation increased in teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Metals implicated in the enhancement of the toxic action of fluoride such as Al were not quantified in this study, but are known to occur at high levels (7,000-12,000 mg/kg) in refining wastes that are land-treated (Loehr et al, 1992). In addition, factors such as nutritional deficiencies (Harris and Navia, 1980) and exposure to Cd (Katsuta et al, 1996) also may induce dental lesions. Cotton rats from land-treatment unit 1 where the most severe dental fluorosis was observed had significantly higher bone concentrations of Sr, Pb, and Ti compared to animals from other land-treatment units.…”
Section: Discussionmentioning
confidence: 99%
“…Black and McKay (1916) first described dental fluorosis induced by exposure to ingested fluoride as a mottling of the enamel. Pathological changes in the enamel organ have been reported in response to various agents, such as fluoride (Neiman & Eisenmann, 1975;, cobalt, strontium (Neiman & Eisenmann, 1975), cadmium (Katsuta et al, 1996), phosphonoformic and phosphonoacetic acids (Caracatsanis et al, 1989) A (Harris & Navia, 1980), vitamin D (Berdal et al, 1989), tetracyclin e (Kallenbach, 1980;Westergaard, 1980), and vinblastin (Moe & Mikkelsen, 1977). Dental fluoritic lesions may range from slight horizontal striation in the enamel (hypomineralization -mottling), moderate or marked mottling or striation, chalkiness with discoloration to hypoplasia (including small tooth size), pitting, and/or thinning and erosion of the enamel (Shupe et al, 1987).…”
Section: Figurementioning
confidence: 99%